Importancia de las organizaciones estudiantiles en la gestión escolar de la escuela de educación general básica Naciones Unidas de la ciudad de Saquisilí, durante el año lectivo 2014-2015 - Chanaluisa Chiliquinga, Laura Amparo (2015)
This present investigative work has been developed in General Basic Education “Naciones Unidas” school is located in Saquisilí Canton guided at teachers, students and parents in order to promote importance student organizations in academic management. In the institution student governments do not fillfull with the work plan, this makes effort does not contribute to the development of establishment, in the investigation work was applied scientific and descriptive research, the same was supported to methods like deductive, inductive and statistics, those allowed to gather information and establish that has not been given adequate importance student governments. Likewise teachers have not encouraged democratic participation and also they do not reflect their responsibility in fulfilling duties like a right representatives of all them to solve the problem in this research, it was established to do a training workshop that will be applied to encourage representatives to work in groups and form new leaders that can fulfill their duties and rights; being very useful in the personal formation and over all democratic. At the end, this present